2020
DOI: 10.3390/pharmaceutics12010061
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer in Vials Nested in a Rack System During Lyophilization

Abstract: Small batch sizes are a consequence of more personalized medicine and reflect a trend in the biopharmaceutical industry. Freeze drying of vials nested in a rack system is a tool used in new flexible pilot scale processing lines. Understanding of heat transfer mechanisms in the rack loaded with vials not in direct contact with each other is necessary to ensure high quality. Lyophilization in the rack vial system enables a homogeneous drying with a reduced edge-vial-effect and shielding against radiation from su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This was already tested thoroughly, e.g. by experiments with heated dryer walls or isolation from radial effects [34]. With this in mind it can be concluded that two critical vials can be identified as representatives for the two relevant boundary cases.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This was already tested thoroughly, e.g. by experiments with heated dryer walls or isolation from radial effects [34]. With this in mind it can be concluded that two critical vials can be identified as representatives for the two relevant boundary cases.…”
Section: Introductionmentioning
confidence: 93%
“…It is well known from literature, that corner vials and vials which face the tray sides or freeze-dryer walls experience a radial heat input [2,[31][32][33]. This was already tested thoroughly, e.g., by experiments with heated dryer walls or isolation from radial effects [34]. With this in mind it can be concluded that two critical vials can be identified as representatives for the two relevant boundary cases.…”
Section: Introductionmentioning
confidence: 94%
“…They confirmed that using a rack system heat transfer can be controlled minimizing the edge vials effect. However, packing density was not evaluated in their work (Daller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%